The Influence of Negative Emotions on Mobile Phone Addiction Among Chinese College Students: The Mediating Role of Negative Coping Styles and the Moderating Role of Gender - Pan J; Guo J; Wu Y; Zhao X (Psychology Research and Behavior Management)
Junxing Pan,1 Junqiao Guo,2 Yangjie Wu,3 Xiaoyun Zhao4 1Department of Students’ Affair, Huaibei Normal University, Huaibei, People’s Republic of China; 2School of Educational Science, Anhui Normal University, Wuhu, People’s Republic of China; 3Department of Education, Bozhou University, Bozhou, People’s Republic of China; 4School of Education, Huaibei Normal University, Huaibei, People’s Republic of ChinaCorrespondence: Xiaoyun Zhao, Email zhaoxiaoyun1980@163.comBackground: Negative emotions (depression and anxiety) are highly correlated with mobile phone addiction among college students, but the underlying mechanisms between variables need further exploration. The aim of this study is to further elucidate the relationship between negative emotions and mobile phone addiction among college students, with negative coping styles as the mediating variable and gender as the moderating variable.Methods: A survey was conducted on 509 college students from two universities in Anhui Province, China, covering topics such as mobile phone addiction, depression, anxiety, and negative coping styles. SPSS software was used to analyze the relationship between variables.Results: Depression, anxiety, negative coping styles, and mobile phone addiction are all significantly positively correlated. Negative coping styles mediate the relationship between depression, anxiety, and mobile phone addiction among college students. Gender regulates the relationship between depression/anxiety and mobile phone addiction. Specifically, the impact of negative emotions (depression and anxiety) on mobile phone addiction is greater in the male group than in the female group.Conclusion: This study further reveals the psychological mechanisms behind the relationship between negative emotions (depression and anxiety) and mobile phone addiction. Negative coping styles are the mediating factor in this relationship, while gender is the moderating factor in this relationship.Keywords: mobile phone addiction, depression, anxiety, negative coping styles, college students, gender